Mycorrhizal Symbiosis Triggers Local Resistance in Citrus Plants Against Spider Mites - Manresa-Grao, María; Pastor-Fernández, Julia; Sanchez-Bel, Paloma; Jaques, Josep A.; Pastor, Victoria; Flors, Víctor (Frontiers in Plant Science, 2022)
Citrus plants are a highly mycotrophic species with high levels of fungal colonization. Citrus aurantium rootstocks typically show abundant root colonization by Rhizophagus irregularis three weeks after inoculation. Mycorrhizal symbiosis protects plants against multiple biotic stressors, however, such protection against spider mites remains controversial. We examined mycorrhiza-induced resistance (MIR) in citrus against the two-spotted spider mite Tetranychus urticae. Mycorrhized C. aurantium displayed reduced levels of damage in leaves and lower mite oviposition rates, compared to non-mycorrhized controls. Mycorrhization did not affect host choice of mites in Y-tube assays; of note, C. aurantium has innate strong antixenotic resistance against this mite. Analysis of metabolism pathways in mycorrhized citrus plants showed upregulated expression of the oxylipin-related genes LOX-2 and PR-3 early after infestation. Accordingly, jasmonic acid (JA), 12-oxo phytodienoic acid (OPDA) and JA-Ile concentrations were increased by mycorrhization. Non-targeted metabolomic analysis revealed the amino acid, oxocarboxylic acid, and phenylpropanoid metabolism as the three major pathways with more hits at 24 hours post infection (hpi) in mycorrhized plants. Interestingly, there was a transition to a priming profile of these pathways at 48 hpi following infestation. Three flavonoids (i.e., malic acid, coumaric acid, and diconiferyl alcohol) were among the priming compounds. A mixture containing all these compounds provided efficient protection against the mite. Unexpectedly, systemic resistance did not improve after 72 h of primary infestation, probably due to the innate strong systemic resistance of C. aurantium. This is the first study to show that MIR is functional against T. urticae in locally infested citrus leaves, which is mediated by a complex pool of secondary metabolites and is likely coordinated by priming of JA-dependent responses.